Constrictive Pericarditis and Rheumatoid Nodules with Severe Aortic Incompetence - Rory Beattie; Karen Booth; Brian Herron; Mary N. Sheppard; Haralambos Parissis (Case Reports in Medicine)
The case of a female patient presenting with constrictive rheumatoid pericarditis and aortic incompetence secondary to valvular rheumatoid nodules is described along with a review of the literature with the aim to highlight this rare cause of aortic insufficiency.